Penilaian Autentik Berbasis Kurikulum 2013 di SD Negeri Mangkubumen Kidul No. 16 Surakarta - Sri Indy Astuti; D. Darsinah (Universitas Muhammadiyah Surakarta, 2019)
This study aims to describe the implementation of planning, implementation, and follow-up of authentic assessments based on the 2013 curriculum in this school. This research is a qualitative descriptive study. The data taken in this study are data on planning, implementation, and follow-up assessment of attitudes, knowledge, and skills. Sources of data from teachers and students in class II and class V as well as school principals. Data collection techniques used are observation, documentation, and interviews. The validity test used is Data Triangulation. The analysis technique used is the Flow Model of Analysis. The results of the study are that the teacher prepares a plan for assessing attitudes, knowledge and skills together with other teachers at one level. The assessment conducted by the teacher is in accordance with the planning and guidelines for assessing attitudes, knowledge, and skills. Followup by the teacher by analyzing, providing guidance, and reporting the results of the assessment of attitudes, knowledge, and skills. Reports of assessment results in the form of numbers, predicates and descriptions.